Determination of Stress in Spread Foundation Subsoil by Various Approaches - Nguyen Giang (Civil and Environmental Engineering, 2015)
The paper deals with the determination of stress induced in spread foundation subsoil by Slovak Technical Standard STN 73 1001:2010 (STN) and Polish Standard PN-81/B-03020 (PN). While STN does not consider with stress state in subsoil just after carrying out excavation and the stress is determined from overloading only, PN considers with stress states after carrying out excavation and follows loading. Differences are also in determination of foundation stiffness and taking into account soil structural strength. It will be shown that different approaches make difference in the value of additional stress up to 18.6 %.